Implementation of Business Ethics on Floating Market Traders Lok Baintan, South Kalimantan - Radhiati, Raisa; Oktaviani; Muhammad Qamaruddin, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The Lok Baintan Floating Market in South Kalimantan is an intangible cultural heritage that is one of the cultural tourist attractions in the city of Banjarmasin. The floating market has existed since the 14th century, although there has been a decline in buyers because infrastructure growth on land has shifted. But currently, apart from buyers from riverside communities, tourists also dominate. The aim of this research is to provide insight into the Islamic business ethics of floating market traders and to increase awareness among floating market traders regarding good business ethics at a time when other businesses are developing rapidly in the modern business era. This research is a descriptive qualitative type of research using field research to provide information, facts, and data regarding the business ethics of Islamic traders at the Lok Baintan Floating Market, South Kalimantan. The population of this research is floating market traders. The sample in this study used a snowball sampling technique, so that 10 main informants were obtained from traders. As for research instruments using observations, interviews, and documentation. Research finds that business ethics is well applied by traders through the principles of unity, free will, equilibrium, responsibility, and benevolence. Although on the principle of free will found ways of forcing approaches and trying to convince buyers to buy, this behavior is just as a strategy of proactive marketing in a customer-seeking approach.